2021
DOI: 10.1002/cjoc.202100263
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pendulum Effect of an Exceptionally Flexible Pillared‐Layer Metal‐Organic Framework

Abstract: Main observation and conclusion Magnifying the controllable directional motions of molecular machines to the macroscopic levels is a significant topic for chemists. Flexible metal–organic frameworks with long‐range order and responsive structural transformation under external stimuli may be an appropriate platform for achieving the target. By taking advantage of the single‐crystal to single‐crystal manner of soft porous crystals, we utilize single‐crystal X‐ray diffraction to directly observe the dynamic struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…[ 5 ] In previous research on functional molecular crystals, hydrogen bonds are not only used as the building blocks of molecular structures, but they can influence structure‐related properties. [ 6‐9 ] Among them, the deuteration effect has been as a strategy to alter the H‐bonds, inducing different properties or producing new characteristics. [ 10‐12 ] For example, hydrogen‐bonded ferroelectric potassium dihydrogen phosphate (KH 2 PO 4 , KDP) has a great phase transition temperature increased by the deuteration effect.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 5 ] In previous research on functional molecular crystals, hydrogen bonds are not only used as the building blocks of molecular structures, but they can influence structure‐related properties. [ 6‐9 ] Among them, the deuteration effect has been as a strategy to alter the H‐bonds, inducing different properties or producing new characteristics. [ 10‐12 ] For example, hydrogen‐bonded ferroelectric potassium dihydrogen phosphate (KH 2 PO 4 , KDP) has a great phase transition temperature increased by the deuteration effect.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Currently there are over 100 000 hits in the Cambridge Structural Database (CSD) MOF subset, 4 which have been widely used in the eld of gas storage/separation, sensing, energy storage, etc. 1,[5][6][7][8][9][10][11][12][13][14] Most MOFs are composed of a single type of ligand and a single type of metallic secondary building unit (SBU), [15][16][17][18] which however limit their structural diversity and functional versatility. By introducing multiple components within the parent network, 19,20 the resulting structurally heterogeneous MOFs, the so-called multivariate MOFs (MTV-MOFs), reported by Yaghi et al 21,22 or solid solution reported by Kitagawa et al, [23][24][25] can largely enhance the structural diversity and functional versatility of MOF contents.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs are a class of porous materials composed of metal-based inorganic nodes and organic linkers . Compared with traditional Zn anode coating materials such as carbon materials, metal oxides, and organic polymers, MOFs excel in the designability and tunability of pore structures and surface properties. The ordered channels of MOFs act as ionic sieves to promote homogeneous Zn 2+ flux and uniform Zn deposition, whereas the insulating nature avoids the growth of Zn dendrites on top of protective layers. For example, the ZIF-8 layer coating on the Zn surface has been shown to homogenize Zn 2+ flux in the ordered micropores and inhibit the growth of Zn dendrites .…”
Section: Introductionmentioning
confidence: 99%